Likert scale and change in range of response categories vs. the factors extraction in EFA model - Tarka, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Abstract: The objective article is the comparative analysis of Likert rating scale based on the following range of response categories, i.e. 5, 7, 9 and 11 in context of the appropriate process of factors extraction in exploratory factor analysis (EFA). The problem which is being addressed in article relates primarily to the methodological aspects, both in selection of the optimal number of response categories of the measured items (constituting the Likert scale) and identification of possible changes, differences or similarities associated (as a result of the impact of four types of scales) with extraction and determination the appropriate number of factors in EFA model. Keywords: Exploratory factor analysis, Likert scale, experiment research, marketing